Portfolio Optimization based Direct Bilateral Matchmaking in Electricity Markets - Muhammad Nauman Rafique (00000172119); Dr. Kashif Imran (USPCAS-E, NUST, Islamabad, 2019)
TH-143
Keywords: MS-EEP Thesis MS Thesis